Microgravity-Induced Alterations of Inflammation-Related Mechanotransduction in Endothelial Cells on Board SJ-10 Satellite - Li, Ning; Wang, Chengzhi; Sun, Shujin; Zhang, Chen; Lü, Dongyuan; Chen, Qin; Long, Mian (Frontiers in Physiology, 2018)
Endothelial cells (ECs) are mechanosensitive cells undergoing morphological and functional changes in space. Ground-based study has provided a body of evidences about how ECs can respond to the effect of simulated microgravity, however, these results need to be confirmed by spaceflight experiments in real microgravity. In this work, we cultured EA.hy926 endothelial cells on board the SJ-10 Recoverable Scientific Satellite for 3 and 10 days, and analyzed the effects of space microgravity on the ECs. Space microgravity suppressed the glucose metabolism, modulated the expression of cellular adhesive molecules such as ICAM-1, VCAM-1 and CD44, and depressed the pro-angiogenesis and pro-inflammation cytokine secretion. Meanwhile, it also induced the depolymerization of actin filaments and microtubules, promoted the vimentin accumulation, restrained the collagen I and fibronectin deposition, regulated the mechanotransduction through focal adhesion kinase and Rho GTPases, and enhanced the exosome-mediated mRNA transfer. Unlike the effect of simulated microgravity, neither three-dimensional growth nor enhanced nitric oxide production was observed in our experimental settings. This work furthers the understandings in the effects and mechanisms of space microgravity on ECs, and provides useful information for future spaceflight experimental design.